The relationship between the match analysis results and ranking of success in Turkish Spor Toto Football Super League - Dag, A.; Özcelik, A. M.; Cele; Çelebi, F.; Aras, D.; Toktas, N. (Kinesiologia Slovenica, 2022)
The purpose of the research was to examine the relationship between ranking of success and match analysis parameters, and to develop a regression formula to understand the effectiveness of these parameters on league score in the season of 2018- 2019 Turkish Spor Toto Football Super League. A total of 306 competitions in the league consisting of 18 teams in the season of 2018-2019 were examined. The parameters used in the current research were total, high intensity, and sprint running distances with or without ball, number of successful shots and passes, ball possessions in the first, second and third regions, and points earned at the end of the season. In accordance with the findings, the most related parameters to the league score were total running distance with ball, and the number of successful shots and passes (p<0.01) and high intensity running distance with or without ball, sprint running distance, successful passes, and shots were mostly seen in the third region in the season of 2018-2019 Turkish Spor Toto Football Super League. The multivariate linear regression analysis F(7,10)=6.05, p=0.0058 was found statistically significant, and showed that 68 % of the variance in the dependent variable (R2 adjusted=0.68) was explained by the ratio of high intensity running distance with ball to high intensity running distance, sprint distance with ball to sprint distance, and the number successful shots and passes. Future studies may also examine the match location, defensive parameters, opposing teams, and other match analysis parameters.